The Comparison Study Among Optimization Techniques in Optimizing a Distribution System State Estimation - Omar, Rosli; Imad Hazim, Hazim; Hazim Mohammed, Imad; N Abdalla, Ahmed; Sulaiman, Marizan; Rasheed, Mohammed (International Journal of Engineering and Technology, 2018)
State estimation considered the main core of the Energy Management System and plays an important role in stability analysis, control and monitoring of electric power systems. Therefore, accurate and timely efficient state estimation algorithm is a prerequisite for a stable operation of modern power grids. These papers introduce an intelligent centralized State Estimation method based on Firefly algorithm for distribution power systems. The mathematical procedure of distribution system state estimation which utilizing the information collected from available measurement devices in real-time. A consensus based static state estimation strategy for radial power distribution systems is proposed in this research. The states of these systems are first estimated through centralized approach using the proposed algorithm to compare with power flow algorithm. The result a proved to be computational efficient and accurately evaluated the impact of distributed generation on the power system. In addition, the proposed FA show faster with increasing the number of buses.Â Â Â